'57 Chocolate: Entrepreneurial Initiatives to Revive Ghana's Chocolate Market. Issue 1 (June 2022) - Ahmed, Jashim Uddin; Talukder, Niza; Khan, Md. Muinuddin; Ahmed, Asma
Ghana, one of the largest suppliers of cocoa in the global market, is widely known for its cocoa beans but not chocolate. A new wave of entrepreneurs emerging from across the African continent are now addressing this issue through efforts to grow the domestic chocolate industry. The case of '57 Chocolate presents an entrepreneurial initiative of two African women who are on a mission to revolutionize the chocolate industry using cocoa beans from Ghana. The case unfolds with a duo of Pan African sisters, Kimberly and Priscilla Addison, passionately using local cocoa to make premium African chocolates that are now available in both local and global markets. In addition to discussing how the brand is standing out in the chocolate market, the case identifies the competitors and goes on to evaluate how the entrepreneurial spirit of the founders is uplifting the image of Ghana.